Phase I Clinical Research of Jejunal Interposition in Adenocarcinoma of the Esophagogastric Junction II/III Proximal Gastrectomy - Kai Tao; Jian-Hong Dong (Gastroenterology Research and Practice)
Objective. To investigate the feasibility and specific methods of single-tract jejunal interposition between esophagus and remnant stomach (ers-STJI) in adenocarcinoma of the esophagogastric junction (AEG) II/III proximal gastrectomy. Methods. 15 AEG II/III gastric cancer (GC) patients in phase T1-3N0M0 with tumor size <5 cm were selected and they underwent proximal gastrectomy with ers-STJI from August 2013 to August 2014. Results. All of the 15 patients successfully completed GC R0 proximal gastrectomy with ers-STJI and no operative death or no significant complication occurred; one patient had anastomotic inflammatory granuloma. The digestive tract reconstruction time was 29.5 ± 5.7 min; the intraoperative blood loss was 96.7 ± 20.2 mL, and the number of lymph node dissections was 21.3 ± 3.0; the postoperative flatus time was 48.2 ± 11.9 h; the average length of hospital stay was 10.7 ± 2.3 d, and the average hospital stay cost was 60 ± 3 thousands. All of the patients were followed up for 12 months, and their postoperative single food intake, body weight, hemoglobin, and albumin were all recovered to the preoperative levels. Conclusions. The applications of ers-STJI in proximal gastrectomy were safe and feasible, and the length of jejunal interposition could be 15–25 cm.